Epidemiology of adverse drug reactions to phenformin and metformin. Issue 6135 (12th August 1978) - Bergman, U; Boman, G; Wiholm, B E
Abstract : Adverse drug reactions (ADRs) to phenformin and metformin reported to the Swedish Adverse Drug Reaction Committee during 1965–77 were analysed in relation to sales and prescription data. The biguanides accounted for 0.6% of all reported adverse drug reactions but for 6% of the fatal cases (all phenformin). Sixty-four ADRs to phenformin and eight to metformin were classified as causal relation "probable" or "not excluded." Fifty-one of these reactions (71%) were lactic acidosis, all but one being reactions to phenformin. After 1973 phenformin was prescribed less in Sweden and metformin became predominant. A nationwide prescription survey during 1975–6 disclosed no differences in age and sex between patients receiving phenformin and metformin. The mean daily doses prescribed in 1976 were 74 mg of phenformin and 1.5 g of metformin. The numbers of ADRs to the two drugs reported during 1975–7 were related to use. The relative incidences of ADRs reported for phenformin and metformin did not differ. Significantly more cases of lactic acidosis and deaths were reported for phenformin.